Long-term effects of azithromycin in patients with cystic fibrosis. (August 2016) - Samson, Clémentine; Tamalet, Aline; Thien, Hoang Vu; Taytard, Jessica; Perisson, Caroline; Nathan, Nadia; Clement, Annick; Boelle, Pierre-Yves; Corvol, Harriet
Abstract: Background: Low-dose azithromycin has beneficial effects on severity of the lung disease in cystic fibrosis (CF) patients for a period of 6–12 months after initiation of the treatment. Although its impact in the longer term is uncertain, this treatment is frequently used chronically. The aim of this retrospective study was to investigate the effects of low-dose azithromycin treatment on the progression of CF lung disease in patients treated for more than 12 months. Methods: All of the CF patients followed in our pediatric center and who had been on low-dose azithromycin for more than 12 sequential months were included. The clinical data were collected for one year before and three years after the initiation of the azithromycin treatment. These data comprised lung function analyses, rates of exacerbations and of antibiotic courses, and changes in the airways' bacterial colonization. Results: A total of 68 patients were included (mean age: 9.95 yrs (3.61)). After 12 months, significant reductions in the numbers of pulmonary exacerbations and antibiotic courses were present. However, this effect was not maintained in the subsequent periods, during which increased rates of both pulmonary exacerbations and antibiotic courses were observed. The lung function decline was not modified during the treatment, and a decreasing time-dependent trend typical of CF was observed for the various parameters. No differences in the airway colonization by pathogens such as Pseudomonas aeruginosa and methicillin-sensitive and/or -resistant Staphyloccocus aureus were observed during the treatment. However, isolated Staphyloccocus aureus strains became resistant to macrolides after 6 months of azithromycin and remained resistant thereafter. Conclusions: No clinical benefits of low-doses azithromycin were present after one year of treatment in young CF patients. Selection for macrolide-resistant strains of bacteria occurred, which should lead to a reconsideration of the duration of azithromycin treatment in CF. Highlights: Low-dose azithromycin treatment is frequently prescribed chronically in cystic fibrosis. During the first year of treatment, it leads to a reduction in the number of exacerbations. This beneficial effect is not maintained in the following years. Selection for macrolide-resistant bacteria occurred after 6 months of azithromycin.